(untitled) (Research, Society and Development, 2020)
Objective: to reflect on the body and sociopoetics in the context of hospital nursing from the socio-communicative meanings. Methodology: this is a theoretical essay, which proposes reflections about the mutual resonance between the conceptual dimensions of the body in the light of sociopoetics and sociocommunicative senses, in a relationship that moves in the context of hospital nursing. Results: evidence the need to increase attention not only to what is verbalized, but also how and what is verbalized and what is not visible in the client or nursing professional participating in the research, especially for its non-verbal manifestations during hospitalization. Conclusion: the constructed sociocommunicative senses obey the principles of the sociopoetic method, because they value the whole body as a source of knowledge: emotional, sensitive, gestural, sensual, rational and imaginative. Unobstructing the senses implies training the perception and thinking about the sensation in relation to the other, through constant dialogue with the body senses themselves and accepting that the clients, through their nonverbal expressions, are continuous sociocommunicatives in the interaction and plural experience, diversified, lived, felt, verbalized, as well as silence or during the behavior exacerbated during care.